The effectiveness of tachosil patch as a drainage and haemostatic agent in thyroid and salivary glands surgeries - Lamry, Nur Adillah (2021)
Objectives: The aim of this study is to evaluate the effectiveness of TachoSil® patch as a drainage and haemostatic agent in thyroid and salivary glands surgeries Method: Twenty-seven patients who undergone thyroid and salivary glands surgeries between June 2018 and May 2020 for benign pathology were included in the study. They were classified into 2 groups; those who did not use TachoSil® patch intraoperatively (known as non-Tachosil group) and those who used TachoSil® patch intraoperatively (known as Tachosil group). Parameters such as duration of surgery, estimated blood loss, post-operative drain amount, duration of drain and duration of hospital stay were used to measure the outcomes in both groups. Result: After 24 hours of surgery, mean drainage volume was reduced in Tachosil group (20mL vs 45mL in non-Tachosil group, p=0.049). Drain removal occurred earlier in the Tachosil group (2 days, as opposed to 2.5days in non-Tachosil group, p=0.045), which resulted in a shorter duration of hospital stay (2 days, as opposed to 2.5d days for non- Tachosil group). Conclusion: This study demonstrated that TachoSil® is beneficial in reducing postoperative drainage volume, which lead to reduction of drain duration, and eventually a reduction in hospitalisation time. Considering that it was significant in providing haemostasis intra-operatively, a bigger sample size future study is needed to adequately assess its effectiveness.